Evolution of the Concept of Barbarism within the Context of the Franco-German Confrontation in the 1870s–1910s - K. S. Antonevich (Концепт: философия, религия, культура, 2024)
Intolerance, demonization and hate speech used to be an integral part of Franco-German relations in the 19th century. The paper is devoted to the analysis of the image of barbarians within the context of the confrontation between France and Germany in 1870s–1910s. Creation and transformation of political myths is viewed through the lens of cultural artefacts. The study is topical because it allows for the analysis of the universal development of cultural confrontation on a specific example. The prime goal of the article is to identify the patterns of mutual stigmatization and account for their seeming anomalies or exceptions to these patterns: the German simultaneously viewed as well-educated and barbarian; common origins of barbarian and classical antique cultures resulting in opposing identities, etc. The aims of the study include: 1) to systematize empirical sources; 2) to assess the impact of historical and cultural context on the formation of the conceptual images of barbaric and civilized; 3) to single out basic dichotomies of the barbaric vs civilized opposition. The study was based on various cultural texts of the period, ranging from speeches, essays, and memoirs to posters and monuments. Methods used included comparative, semiotic, and imagological approaches, corpus, discourse, and content analyses. French newspaper clichés are compared to the Europe-wide opinions about Prussian militarism. As it turns out, the German way of thinking about the heroes of the past contributed to political stigmatization of Germany. Another finding, based on French literature, is the unobvious correlation between decadent world perception and political turmoil in France. Modernist poetry, literature and journalism compared the fall of the French Empire to the collapse of the Roman Empire and thus contributed to the conceptualizing of the German as barbarians. At the same time German propaganda attempted to defend itself by finding barbarians on the east and ironically quoting French sources to speak about actual war crimes. The results of the study show that seemingly chaotic hate speech and confrontation are determined on the basis of the specific rules related to age-old non-political traditions and current political circumstances marking the dichotomy between oneself and the other, friend or foe.